2020
DOI: 10.1093/schbul/sbaa099
|View full text |Cite
|
Sign up to set email alerts
|

Anterior vs Posterior Hippocampal Subfields in an Extended Psychosis Phenotype of Multidimensional Schizotypy in a Nonclinical Sample

Abstract: Numerous studies have implicated involvement of the hippocampus in the etiology and expression of schizophrenia-spectrum psychopathology, and reduced hippocampal volume is one of the most robust brain abnormalities reported in schizophrenia. Recent studies indicate that early stages of schizophrenia are specifically characterized by reductions in anterior hippocampal volume; however, studies have not examined hippocampal volume reductions in subclinical schizotypy. The present study was the first to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 99 publications
7
33
1
Order By: Relevance
“…Correct responses potentially reflect semantic information reserve capacities, while semantic intrusion errors could be considered as failures in semantic processing either due to poor strategic search of representations classified according to their meaning or misattribution of meaning to representations. It is of note, that disorganized schizotypy has been associated with a wide neural network encompassing several brain structures, such as the superior longitudinal fasciculus ( 121 ), hippocampus ( 123 ), and superior temporal gyrus ( 124 ), that are crucial for semantic processing ( 125 131 ), thus proving a plausible explanation for our finding. The fact that the association of disorganized schizotypy and semantic processing was abolished in the “schizotypy congruent” sub-group is most probably to the smaller sample size of this group resulting in limited variation of semantic fluency intrusion errors that is required for associational analyses.…”
Section: Discussionsupporting
confidence: 65%
“…Correct responses potentially reflect semantic information reserve capacities, while semantic intrusion errors could be considered as failures in semantic processing either due to poor strategic search of representations classified according to their meaning or misattribution of meaning to representations. It is of note, that disorganized schizotypy has been associated with a wide neural network encompassing several brain structures, such as the superior longitudinal fasciculus ( 121 ), hippocampus ( 123 ), and superior temporal gyrus ( 124 ), that are crucial for semantic processing ( 125 131 ), thus proving a plausible explanation for our finding. The fact that the association of disorganized schizotypy and semantic processing was abolished in the “schizotypy congruent” sub-group is most probably to the smaller sample size of this group resulting in limited variation of semantic fluency intrusion errors that is required for associational analyses.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with previous findings suggesting that failure to distinguish between positive and negative schizotypy dimensions could result in reduced estimator robustness (Barrantes-Vidal, Gross, et al, 2013;Barrantes-Vidal, Lewandowski, & Kwapil, 2010), we found differences in the direction between the regressors that reflect the unique explanatory contribution of each schizotypy dimension. The significant main effect of the positive dimension is not confirmed by our previous study (Sahakyan et al, 2021) with the Multidimensional Schizotypy Scale (MSS; Kwapil, Gross, Silvia, Raulin, & Barrantes-Vidal, 2018). This inconsistency may be attributed to differences between psychometric instruments that provide three (MSS) or four (O-LIFE) phenotype dimensions entered as model predictors.…”
Section: Left Subiculumcontrasting
confidence: 73%
“…This study protocol was in agreement with the Declaration of Helsinki (World Medical Association, 2013) healthy adults (Mean age = 23.85, SD = 3.75 years, min = 18, max = 39) included in the analysis. In this study, we extended the sample previously described in Sahakyan et al (2021). Seven (1.91%) participants scored PLE equal to or above the CHR screening criteria applied in previous studies (Chen et al, 2016;Ising et al, 2012).…”
Section: Study Cohortmentioning
confidence: 97%
“…Association of the MSS subscales with hippocampal volume. Sahakyan et al (2021) examined the associations of MSS positive, negative, and disorganized schizotypy dimensions with hippocampal subfield volumes in a large sample (n = 195) of nonclinically ascertained young adults. Hippocampal subfields were analyzed from high-resolution 3 Tesla structural magnetic resonance imaging scans testing anatomical models, including anterior vs posterior regions and the cornu ammonis (CA), dentate gyrus (DG), and subiculum subfields separately for the left and right hemispheres.…”
Section: Section 5 Validity Of the Mssmentioning
confidence: 99%